Determinantes da oferta de exportação de mangas: estudo de caso para o Brasil e o Peru - Arévalo, Jorge Luis Sánchez (Universidade Federal do Tocantins, 2016)
The mango is one of the most consumed fruits worldwide and most exported by Brazil and Peru. For the year 2009, according to FAO data (2012) both countries occupied the fourth and, the sixth place among exporting countries worldwide. Therefore, the objective of this study was to analyze the determinants of mango exports by Brazil and Peru, focusing on the main export destination markets, as markets are U.S. and EU for the period 2000 to 2011, the so that both businesses and governments can take into account the effects that cause the variables used in the quantity exported. For this analysis, we used the method of Self - Regression Vector Error-correction - VEC. The variables used to explain the determinants of export of mangoes were: for Brazil, domestic prices of mango in Brazil, U.S. wholesale prices, wholesale prices in the EU, U.S. domestic income (GDP proxy), EU domestic income (GDP proxy) and, the exchange rate euro / Dollar. For Peru, domestic prices of mango in Peru, U.S. wholesale prices, wholesale prices in the E.U., U.S. domestic income (GDP proxy), EU domestic income (GDP proxy) and, the exchange rate Euro / Dollar. The results for Brazil show that domestic prices as well as wholesale prices in the U.S. show expected results for the quantity exported, but given a shock (impulse) in these variables the effect on the quantity exported shows an unexpected result, with a drop the quantity exported to a surge in wholesale prices in the U.S. and, growth in the quantity exported to a shock on domestic prices, in this context, we emphasize, that domestic prices are influenced by the behavior of the external market. The results for Peru shown that only domestic prices have expected results, given the negative coefficient, so if domestic prices rise, decreases the quantity exported. Importantly, the income EU, proved crucial to explain positively the quantity exported by Peru, to a shock (impulse) in this explanatory variable. In summary, the significance of domestic prices, may explain the strong consumption that both countries have.